Analisa Pemasaran Platform P2P Lending Syariah pada PT Alami Fintek Sharia - Saifuddin Saifuddin; M Hadziq Affan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research is focused on the investatation  marketing strategy of Peer to peer lending investment at PT. Alami Fintek Sharia (Alami). The purpose of this research is to improve the marketing strategy of the Fintech P2P (Alami) marketing platform to increase consumers in UMKM funding. The main theory is Marketing Mix (4P). The object of this research is the marketing strategy of the marketing team at PT. Alami Fintek Sharia (Alami). The research method used  qualitative with a library research approach. The results of this research are  the products that  offered by Alami are different from other products and provide benefits for users so that users can attract consumers' purchasing power. The price offered is also affordable, this is also one of the attractions for consumers to help determinings their choice in investing using Alami.